A study on the structural characteristic of tire clamp using a new design method - Ji-Qiang Li; Ling-Zhi Nie; Shu-Fan Feng; Tong Wu; Jeong-Tae Kwon; Bao-Wei Wang; Ji-Chao Li; Xiang-Dong Li (Advances in Mechanical Engineering)
The development of the new energy automobile industry has driven the development of the tire industry, and the development of the tire industry has put forward higher requirements for the handling and storage efficiency of tires. In this paper, through the discussion of the new tire synchronous fixture, the double parallel four-bar mechanism is introduced. The mechanism has the advantages of horizontal extension and contraction, and avoids the deviation in the vertical direction. In order to be better applied to the handling and storage of tires and further applied in other fields, this paper obtains the relationship between rod length and stroke through the kinematic analysis of double parallel four-bar mechanism, establishes a compact structure size table of common size, and carries out practical application simulation. The accuracy of size is verified by mechanical simulation. Through the relationship established in this paper and the compact structure size table, we can quickly and easily find the appropriate size of the double parallel four-bar mechanism according to the demand. Through the study of its structural characteristics, we can easily find the scene where it can be applied, so as to promote the universality of the application of the double parallel four-bar mechanism.